Epiphyseal Closure Time of Radius and Ulna Bones of the Proximal Section - Lio, Tiara Mayang Pratiwi; Koesbardiati, Toetik; Yudianto, Achmad; Setiawati, Rosy (Folia Medica Indonesiana, 2018)
Accurate determination of age is important in the legal process; when a person's age is unknown or must be authenticated, a forensic age identification method must be applied. One of such methods is to assess the epiphyseal closure on the bone through radiological examination. The main problem associated with the use of this method is the relevance of the reference population provided because epiphyseal closure is influenced by genetics and nutrition. This method needs data to represent each population. Radiological examination of elbow bones of 30 male patients aged 11-30 years and 18 female patients aged 14-28 years in Dr. Soetomo Hospital, Surabaya from January to April 2016 was carried out to determine the time of epiphyseal closure of the radius and ulna distal section. This was cross-sectional descriptive study. In conclusion, epiphyseal closure of proximal radius and ulna is complete at age 16 in males and 14 in females.